Functional Food Processing Application as PMT (Providing Additional Food) for BADUTA in the Program to Support the Movement to Prevent Stunting in Medan Deli District - Vivi Asfianti; Denny Satria; Ahmad Hafizullah Ritonga; Ahmad Fadli; Alfi Sapitri (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is a form of growth failure due to the accumulation of inadequate nutrition that lasts for a long time starting from pregnancy until the age of 24 months, characterized by body length or height being below standard, based on the PB/U or TB/U index, the results of these measurements are at the threshold < -2 SD, =-3 SD (short) and <-3 SD (very short). Based on WHO data (2020), the prevalence of stunting in children under five in the world is 149.2 million or around 22%, the national prevalence of stunting in 2022 is 21.6%, the prevalence of stunting in North Sumatra (January 2023) reaches 21.1%, ranked 17th from 34 provinces with the highest number of stunted children in Indonesia. The prevalence of stunting in Medan City (as of April 1 2023) is 298 children under five. Data obtained from the Medan Deli District Family Planning Coordinator, currently there are 28 stunted toddlers and 30 stunted toddlers, of the 28 stunted toddlers, 1 toddler has 'graduated' from stunting. The aim of this service is to apply functional food processing as PMT (Supplemental Food Provision) for BADUTA as an effort to support the Stunting Prevention Movement Program in accordance with PERPRES (2021) No. 72. In the outreach activities, pretest and posttest evaluation activities were carried out to determine the level of knowledge of participants regarding the provision of additional protein-rich functional food (PMT) in the form of cereal cookies to stunted toddlers and those at risk of stunting by providing simple choice questions that they had to answer. The results of the service obtained are functional stunting food products in the form of cookies containing porang flour and moringa